Propuesta de un reglamento, y un manual de seguridad industrial y salud ocupacional para la “Mecánica Industrial Aguirre” de la ciudad de Yanzatza - Obaco Pardo, Ángel Eduardo (2015)
This paper titled "PROPOSAL FOR A REGULATION AND A MANUAL FOR OCCUPATIONAL SAFETY AND HEALTH BODY FOR INDUSTRIAL CITY AGUIRRE Yanzatza" general objective is to propose a manual safety and occupational health for the company Industrial mechanics Aguirre and specific objectives, determining the situational analysis of industrial safety and occupational health of the company, identify, specify and assess the risks of work, establish procedures to help consolidate, reformulate or implement preventive measures to reduce risks changing the work environment, plan the delivery of personal protective equipment specifically to the needs of each area, composing training policies and plans aimed at reducing unsafe within the plant acts, submit the proposal manual Industrial health and Safety, thus giving compliance to the general objective of the subject. Also, this work has had its full theoretical foundation that has served to strengthen the information obtained; the methods used are: Descriptive, helped establish criteria to find the problem of implementing a manual Industrial safety and occupational health inductive; to analyze respectable amounts of information and to raise the findings, deductive put forth a proposal to design a manual safety and occupational health to serve as a tool the manager of Mechanical Industrial Aguirre, statistical allowed graphically describing the results based on the surveys workers, and the interview that the manager manage Industrial Mechanics Aguirre; deductive allowed to apply general theories related to industrial safety and occupational health in the investigated 5 industrial mechanics and develop the respective, regulation and manual; Analytical Synthetic; Was used to analyze and synthesize information obtained in relation to major risk factors and how to minimize them, according to the rules that will arise for mechanical investigated; the techniques used to collect data are set out below: Observation used by visiting the company premises, Interview applied to the Managing Owner of the company that helped identify strengths and weaknesses and obtain primary information for the development of research, survey applied to employees of the same company that allowed for the internal analysis of the company; between the main results were obtained: In the interview with the owner manager was able to determine the strengths and weaknesses of the company, with the result that the knowledge of Industrial Safety are basic, for proper safety when conducting their business activities, the company has no signage, Industrial Mechanics Aguirre has no policies, regulations and rules of industrial safety; besides you can highlight that 81.82% do not have knowledge about the application of Industrial Health and Safety Manager has managed to provide its employees with personal protective equipment and informs the staff about the risks and precautions to consider when using machinery or engaging in productive processes. Finally after having performed the analyzes were determined as central proposal "PROPOSAL FOR A REGULATION AND A MANUAL FOR OCCUPATIONAL SAFETY AND HEALTH BODY FOR INDUSTRIAL CITY AGUIRRE Yanzatza"